SEISMOSTRATIGRAPHIC JUSTIFICATION OF JOINT DEVELOPMENT POSSIBILITY OF MINERAL SALT AND HYDROCARBON DEPOSITS - Sanfirov, I.A.; Nikiforova, A.I.; Kalashnikova, M.M.; Zhikin, A.A. (Perm Federal Research Centre Journal, 2017)
12 oil deposits, connected with reef structures of the Late Devonian-Tournaisian age, have been opened within the Upper Kama potash deposit. Their exploitation is difficult or impossible without damage to the potash deposit. Impact analysis of the reef structures on the structural features of the potash deposit has been performed. The formation of weakened zones in the salt thickness has been found with the help of direct (well drilling, sampling) and remote (seismic surveys, geochemical sampling) studies. The connection between the reef facies and weakened zones of waterproof thickness of the potash deposit, determining possibilities of the development of oil deposits, is shown. A method for evaluating the complexity of the structure and deterioration of the salt thickness over the reefs of the Bereznikovskoe paleoplateau has been developed based on mutually complementary study of subsalt and saliferous rock complexes.